Practice patterns of female urologists in Australia and New Zealand. (17th October 2018) - Johns Putra, Lydia; Cheng, Janice; Dowling, Caroline; Clarke, Anita
Abstract : Objective: To analyse the practice patterns of female urologists in Australia and New Zealand. Participants and Methods: An electronic survey was sent to female urologists and urology trainees of the Urological Society of Australia and New Zealand in December 2016, with questions on demographics, practice patterns and views on mentorship. Results: Of 82 recipients of the questionnaire, 60 (73.2%) responded. Of these, 61.7% were aged <40 years, 81.7% were married or in a long‐term relationship and 56.7% had children. A total of 67.8% had completed urology training. Of these, most had commenced clinical practice within the preceding 12 years, most had taken no time off in training and most had taken <1 year away from clinical practice. A total of 74.4% practised in a metropolitan area and 42.5% described their practice as being general urology. High or moderate satisfaction levels were reported by 88.1% of respondents and 92.9% intended to retire before the age of 70 years. A total of 17.2% had not had a mentor and 80.7% thought a mentorship scheme would be useful. Conclusion: These results provide information on the practice patterns of the increasing number of women urologists in Australia and New Zealand and have the potential to shape workforce and training planning in this region and worldwide.